A Gene Variation at the ZPR1 Locus (rs964184) Interacts With the Type of Diet to Modulate Postprandial Triglycerides in Patients With Coronary Artery Disease: From the Coronary Diet Intervention With Olive Oil and Cardiovascular Prevention Study - Alcala-Diaz, Juan F.; Arenas-de Larriva, Antonio P.; Torres-Peña, Jose D.; Rodriguez-Cantalejo, Fernando; Rangel-Zuñiga, Oriol A.; Yubero-Serrano, Elena M.; Gutierrez-Mariscal, Francisco M.; Cardelo, Magdalena P.; Luque, Raul M.; Ordovas, Jose M.; Perez-Martinez, Pablo; Delgado-Lista, Javier; et al. (Frontiers in Nutrition, 2022)
Background and aims: rs964184 variant in the ZPR1 gene has been associated with blood lipids levels both in fasting and postprandial state and with the risk of myocardial infarction in high-risk cardiovascular patients. However, whether this association is modulated by diet has not been studied. Objective: To investigate whether the type of diet (low-fat or Mediterranean diets) interacts with genetic variability at this loci to modulate fasting and postprandial lipids in coronary patients. Methods: The genotype of the rs964184 polymorphism was determined in the Cordioprev Study population (NCT00924937). Fasting and Postprandial triglycerides were assessed before and after three years of dietary intervention with either a Mediterranean or a low-fat diet. Postprandial lipid assessment was done by a 4-hour oral fat tolerance test (OFTT). Differences in triglycerides levels were identified using repeated-measures ANCOVA. Results: From 523 patients (85% males, mean age 59 years) that completed the OFTT at baseline and after 3 years of intervention and had complete genotype information, 125 of them were carriers of the risk allele G. At the start of the study, these patients showed a higher fasting and postprandial TG plasma levels. After three years of dietary intervention, G-carriers following a Mediterranean Diet maintained higher fasting and postprandial triglycerides, while those on the low-fat diet reduced their postprandial triglycerides to similar values to the population without the G-allele. Conclusions: After three years of dietary intervention, the altered postprandial triglyceride response induced by genetic variability in the rs964184 polymorphism of the ZPR1 gene can be modulated by a low-fat diet, better than by a Mediterranean diet, in patients with coronary artery disease.